Exploration Mathematical Communication Skills: A Comprehensive Analysis of Students' HOTS Problem-Solving Based on Learning Styles - Amany, Azzah; Rahmawati , Dian Davi; Setyaningsih, Nining (Universitas Negeri Semarang, 2024)
This research explores students' mathematical communication skills in solving Higher Order Thinking Skill (HOTS) problems, considering visual, auditory, and kinesthetic learning styles. The study aims to describe students' mathematical communication abilities and understand how learning styles influence these capabilities. A qualitative descriptive research method was employed, involving second-semester seventh-grade students at MTs Negeri 1 Pacitan. Data collection comprised learning style questionnaires, mathematical communication skills tests, and interviews. Results indicate that students with visual learning styles effectively conveyed situations and explained problem-solving strategies but lacked precision in validating arguments. Auditory learners demonstrated proficiency in all four indicators of mathematical communication skills, including argument validation. Kinesthetic learners, while capable of stating situations, encountered difficulties in elucidating problem-solving strategies and did not engage in argument validation.